The Role of Extra-role Behavior in Improving Public Service Quality: A Literature Review - Miarni, Isra; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This paper aims to critically examine the role of extra-role behavior (ERB) or organizational citizenship behavior (OCB) in improving the quality of public services in Indonesia. It uses a systematic literature review of seven relevant national scholarly articles and synthesizes findings on how various dimensions of OCB such as altruism, conscientiousness, sportsmanship, civic virtue, and individual initiative contribute to effectiveness and satisfaction within the context of public service. This study highlights the significant role of public service motivation (PSM) as a primary antecedent of OCB in Indonesia’s public sector and the influence of contextual factors such as leadership and reward systems in fostering extra-role behavior. The novelty of this review lies in the in-depth integration of national literature within the context of Indonesian public services, synthesis of the interaction between PSM and OCB dimensions, articulation of the implications of OCB dimensions on service mechanisms, contextual perspectives on OCB antecedents, and the identification of future research agendas relevant to the specific characteristics of Indonesia’s public sector. This review concludes that OCB is a crucial asset in enhancing the quality of public services and recommends that public sector organizations develop strategies that promote and appreciate employees’ extra-role behavior.